Strengthening Teachers of the School of Movement in the Implementation of the Independent Curriculum through Training in Developing Project Modules Based on Local Wisdom in Grobogan Regencyodules Based on Local Wisdom in Grobogan Regency - Oktarina, Nina; Widodo, Joko; Murtadlo, Muhammad Nukha; Wijaya, Angga Pandu; Suryanto, Edy; Maulida, Syakila; Puspita, Amanda Dewi (Universitas Negeri Semarang, 2024)
The implementation of the Merdeka Curriculum since 2022 has brought significant changes to education in Indonesia. Learning activities in schools now consist of intramural and co-curricular activities, including the Project to Strengthen the Pancasila Student Profile (P5), alongside extracurricular activities. A new addition to the curriculum is the P5, which was absent from previous curricula. In practice, many teachers face challenges in planning P5 learning, particularly in developing project modules based on local wisdom. This challenge is due to the limited understanding of P5, and not all teachers have been certified as part of the